Historisitas dan Tujuan Aturan Umur Minimal Perkawinan dalam Perundang-Undangan Keluarga Islam di Indonesia - Ulfi Azizah; Nur Wahid (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2019)
This paper examines the minimum age requirement for marriage in Indonesian family law legislation in Indonesia historically. Determination of the minimum age for marriage in various countries is the result of ijtihad by considering the principle of physical and psychological maturity. In Indonesian marriage legislation sating that marriage is only permitted if the man reaches the age of 19 (nineteen) years and the woman has reached 16 (sixteen) years. Early marriage has several risks such as potential premature births, birth defects, maternal depression rates, maternal mortality rates, risk of contracting sexually transmitted diseases. Therefore, the authors strongly agree that the minimum age of marriage in Indonesia changed to 19 years